O papel do professor para orquestrar mediações como espaços de leitura crítica - Queiróz, Sandra Regina de Bitencourt (2009)
This work aims to examine my own professional training in a new social practice of reading proposed by GEIM (Grupo de Estudos da Indeterminação e da Metáfora Group of Studies on Indeterminacy and Metaphor) in the form of a critical research-action (Kincheloe, 1993). This Applied Linguistics research discusses, according to a social-historic cultural perspective (Vygotsky, 1934) two reading experiences mediated by the technique of Group Think Aloud (Zanotto, 1995, 1998, 2007). I developed the critical research-action (Kincheloe, 1993) using a qualitative interpretivist research methodology (Erickson, 1986 and Moita Lopes, 1994), examining my action as voice mediator and orchestrator of pupils in Group Think Aloud, about text interpretation in the classroom context. Research subjects were two groups of female pupils of the 7th grade of primary education in a State public school. Resources for data collection were the Group Think Aloud technique (Zanotto, 1995, 1998, 2007), the retrospective questionnaire and the reflexive notebook (Machado, 1998). Data analysis showed as results (a) Group Think Aloud was an important pedagogic tool that encouraged pupils to argument and favored a critical reading activity by them; (b) the use of questions was an interesting mediation tool, encouraging reflection and participation and arousing interest; (c) my action was transformed, which stopped being that of someone who has the knowledge to be that of a mediator, not seeing pupils as empty recipients any more and beginning to understand them as being agents in the construction of sense